The Determinants of Income Equality in Bangka Belitung Province - Redita, Nesha; Robiani, Bernadette; Yulianita, Anna (Journal of Economic Development, Environment and People, 2021)
Abstract. The income distribution phenomenon in Bangka Belitung Islands Province during the 2007-2018 period became the basis for analyzing the determining variables of income distribution including the industrial sector, the agricultural sector, the trade sector, and the industrial labor productivity. We measured the income distribution indicator from the Gini coefficient value used the Panel Data Regression approach to determine the effect of these variables on the Gini coefficient in all regencies/cities in the Bangka Belitung Islands Province. The results showed that the determinant of the income distribution was the agricultural sector. Further findings prove that the agricultural, industrial, and trade sectors improved income distribution. Keywords: Income Inequality, industrial sector, agricultural sector, industrial labor productivity